SPATIAL CONTROL TO REDUCE URBAN HEAT ISLAND EFFECT IN URBAN HOUSING - Nurrahmi Kartikawati; Arif Kusumawanto (Journal of Architecture&ENVIRONMENT, 2013)
As the world’s issue of global warming, built environment has to be designed to reduce global warming effects such as urban heat island. A large building coverage with small amount of vegetation tends to have urban heat island effect. Some urban housing have typical spatial character that trigger urban heat island effect. Some physical aspects give wide contribution to urban heat island effects, such as space configuration, vegetation and land coverage. The influences of these aspects can be observed by simulating the aspects. As the heritage preservation region, some urban housing such as Kauman Jogjakarta can’t be redesigned by changing its main buildings. Therefore, space configuration changing in a simulation can help to know the influence of space configuration type to thermal comfort of the region. Choosing the right material type to cover the soil will give a good contribution to reduce temperature. The presence of vegetation with various types can reduce heat expose to the areas. Some types of vegetation give a big contribution to reduce temperature. As the material study, choosing the right type of vegetation can reduce temperature and increase microclimate comfort. Areas with high density leafs plants give better contribution to microclimate comfort. High dense leaf plants in existing area were planted with certain pattern. The existing space configuration as perpendicular circulation pattern gives better microclimate condition than random pattern. There are some aspects to reduce the urban heat island effect in urban housing by controlling urban housing space on three main aspect: land coverage, vegetation and space configuration.